2005
DOI: 10.1086/431975
|View full text |Cite
|
Sign up to set email alerts
|

RAPTOR Observations of the Early Optical Afterglow from GRB 050319

Abstract: The RAPid Telescopes for Optical Response (RAPTOR) system at Los Alamos National Laboratory observed GRB 050319 starting 25.4 s after g-ray emission triggered the Burst Alert Telescope (BAT) on board the Swift satellite. Our well-sampled light curve of the early optical afterglow is composed of 32 points (derived from 70 exposures) that measure the flux decay during the first hour after the GRB. The GRB 050319 light curve measured by RAPTOR can be described as a relatively gradual flux decline (power-law index… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 23 publications
5
54
0
Order By: Relevance
“…Vreeswijk et al (2008a). (1) Huang et al (2007); (2) Kamble et al (2007); (3) Woźniak et al (2005); (4) Cobb & Bailyn (2005); (5) Rosenberg & Garnavich (2005); (6) Flasher et al (2005); (7) Yanagisawa et al (2005); (8) Homewood et al (2005); (9) Mirabal et al (2005); (10) Pandey et al (2006); (11) Macomb et al (2005); (12) Cenko et al (2006b); (13) Durig & Price (2005); (14) Jakobsson et al (2005b); (15) Andreev & Pozanenko (2005); (16) Henych et al (2005); (17) Piranomonte et al (2005); (18) D'Elia et al (2005); (19) Alatalo et al (2006); (20) Curran et al (2007); (21) Stanek et al (2007); (22) Woźniak et al (2006); (23) Molinari et al (2007); (24) Nysewander et al (2006); (25) …”
Section: Xrt Datamentioning
confidence: 99%
“…Vreeswijk et al (2008a). (1) Huang et al (2007); (2) Kamble et al (2007); (3) Woźniak et al (2005); (4) Cobb & Bailyn (2005); (5) Rosenberg & Garnavich (2005); (6) Flasher et al (2005); (7) Yanagisawa et al (2005); (8) Homewood et al (2005); (9) Mirabal et al (2005); (10) Pandey et al (2006); (11) Macomb et al (2005); (12) Cenko et al (2006b); (13) Durig & Price (2005); (14) Jakobsson et al (2005b); (15) Andreev & Pozanenko (2005); (16) Henych et al (2005); (17) Piranomonte et al (2005); (18) D'Elia et al (2005); (19) Alatalo et al (2006); (20) Curran et al (2007); (21) Stanek et al (2007); (22) Woźniak et al (2006); (23) Molinari et al (2007); (24) Nysewander et al (2006); (25) …”
Section: Xrt Datamentioning
confidence: 99%
“…A particular cautionary tale is GRB 050319. The original analysis of early optical data showed a shallow light curve break, when using the BAT trigger time Woźniak et al (2005). Further analysis of BAT slew data demonstrated that the main GRB event was in fact 137 s prior to the original BAT trigger time (Chincarini et al 2005).…”
Section: Estimating γmentioning
confidence: 99%
“…However, the cessation of early energy injection would be expected to produce an achromatic light curve break, which is not generally observed (e.g., Panaitescu et al 2006;Fan & Piran 2006), although interpretation of X-ray breaks is not always straightforward (Racusin et al 2009). Observations of individual bursts (e.g., Akerlof et al 1999;Smith et al 2003;Rykoff et al 2004Rykoff et al , 2006bWoźniak et al 2005;Quimby et al 2006;Vestrand et al 2006;Romano et al 2006;Molinari et al 2007;Schady et al 2007) have been interpreted in the context of various models. It is clear that for most early afterglows the "closure relationships" (e.g., Granot & Sari 2002), which compare the spectral index of the synchrotron emission to the temporal decay Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Data for GRB 021004 are from Fox et al (2003a) and GCNCs 1564GCNCs , 1566GCNCs , 1570GCNCs , 1573GCNCs , 1576GCNCs , 1577GCNCs , 1578GCNCs , 1580GCNCs , 1581GCNCs , 1582GCNCs , 1584GCNCs , 1587GCNCs , 1591GCNCs , 1594GCNCs , 1606GCNCs , 1614GCNCs , 1615GCNCs , 1628. Data for GRB 050319 are from Woźniak et al (2005) and GCNCs …”
Section: Early Optical Grb Afterglowsmentioning
confidence: 99%